Molecular transition frequencies of CO2 near 1.6 µm with kHz-level uncertainties. (September 2021) - Reed, Z.D.; Drouin, B.J.; Long, D.A.; Hodges, J.T.
Highlights: We used CL-CRDS referenced to a Cs clock to measure a total of 44 CO2  transition frequencies in the (30012) ← (00001) and the (30013) ← (00001) bands with kHz-level uncertainties. We performed a global fit of an effective Hamiltonian to the present data and literature values to yield spectroscopic parameters for the four involved states. This analysis provided best-case rms fit residuals of 4 kHz for the (30013) ← (00001) band. We observed a Fermi resonance in the (30012) ← (00001) band, identified the perturbing state as (33301) and measured an effective interaction parameter between these two upper states. Incorporation of the resonance interaction reduced global fit residuals by a factor of 25 for the 30012 band, yielding residuals near 10 kHz. The high accuracy of these transition frequency measurements makes these results suitable as SI-traceable reference data. Abstract: We present measurements of molecular transition frequencies based on the comb-locked cavity ring-down spectroscopy technique, reporting vacuum transition frequencies of Doppler-broadened 12 C 16 O2 in the 1.6 μm region for the (30012) ← (00001) and (30013) ← (00001) bands with an average combined standard uncertainty of ≈ 1 kHz. A global four-state model was fit to these data and literature values to provide spectroscopic parameters and a best-case fit precision of 4 kHz. We identified and quantified an interaction between the (30012) and (33301) states which was manifest as an observed Fermi-resonance-type perturbation in the (30012) ← (00001) band. This interaction was accounted for in the global fit, substantially reducing systematic uncertainties in the spectroscopic parameters of the (30012) state and altering many predicted transition frequencies in the (30012) ← (00001) band by 1 MHz or more relative to literature values. The accurate transition frequencies reported here may be considered as SI-traceable reference data for diverse applications including remote sensing and telecommunications.